Optimizing biodiversity gain of European agriculture through regional targeting and adaptive management of conservation tools. (January 2020) - Concepción, Elena D.; Aneva, Ina; Jay, Marion; Lukanov, Simeon; Marsden, Katrina; Moreno, Gerardo; Oppermann, Rainer; Pardo, Adara; Piskol, Stephan; Rolo, Víctor; Schraml, Antonia; Díaz, Mario
Abstract: Agricultural intensification continues being a major threat for biodiversity worldwide. Despite the incorporation of diverse conservation tools in the Common Agricultural Policy (CAP) since the 1990s, European agriculture continues intensifying. The last CAP reform introduced compulsory greening, including measures to support semi-natural habitats across the wider countryside (referred to in this paper as Green and Blue Infrastructure, GBI), and by these means biodiversity. However, the actual benefits of greening implementation have not been evaluated formally through field studies, and its effectiveness is questioned. We assess the capacity of a variety of GBI features that can be supported by CAP greening to promote biodiversity across a variety of agricultural systems. We analyze the relationships between diversity (birds and plants) and a set of habitat indicators linked to distinct greening options in 115 plots from six case study areas, including arable land, pastures and mixed farming systems in Spain, Germany and Bulgaria. Relationships between biodiversity and the different GBI elements varied considerably between regions, systems and organisms' groups. Some of these relationships were non-linear. Although most GBI elements showed potential for promoting biodiversity, they should be adapted to specific conservation targets and landscape constraints regionally. The next CAP reform could include compulsory measures that support connectivity, heterogeneity and small-landscape elements characteristic in each region (e.g. field margins and trees or preventing field size enlargement), combined with more regionally-orientated voluntary measures (e.g., promoting grassland and fallow). Performance evaluation and adaptation ought to accompany the implementation of these measures to ensure their ecological success. Highlights: Biodiversity-habitat relationships greatly vary among regions and organisms' groups. Some of these relationships were non-linear and less significant in complex systems. Small field size, connectivity and landscape elements supported overall diversity. Small field size, grassland and fallow favoured farmland specialists Permanent and cover crops, agroforestry and crop diversification had fewer benefits